Phenotypic Screening Identifies Synergistically Acting Natural Product Enhancing the Performance of Biomaterial Based Wound Healing - Sivasubramanian, Srinivasan; Chandrasekar, Gayathri; Svensson Akusjärvi, Sara; Thangam, Ramar; Sathuvan, Malairaj; Kumar, R. B. S.; Hussein, Hawraa; Vincent, Savariar; Madhan, Balaraman; Gunasekaran, Palani; Kitambi, Satish S. (Frontiers in Pharmacology, 2017)
The potential of multifunctional wound heal biomaterial relies on the optimal content of therapeutic constituents as well as the desirable physical, chemical, and biological properties to accelerate the healing process. Formulating biomaterials such as amnion or collagen based scaffolds with natural products offer an affordable strategy to develop dressing material with high efficiency in healing wounds. Using image based phenotyping and quantification, we screened natural product derived bioactive compounds for modulators of types I and III collagen production from human foreskin derived fibroblast cells. The identified hit was then formulated with amnion to develop a biomaterial, and its biophysical properties, in vitro and in vivo effects were characterized. In addition, we performed functional profiling analyses by PCR array to understand the effect of individual components of these materials on various genes such as inflammatory mediators including chemokines and cytokines, growth factors, fibroblast stimulating markers for collagen secretion, matrix metalloproteinases, etc., associated with wound healing. FACS based cell cycle analyses were carried out to evaluate the potential of biomaterials for induction of proliferation of fibroblasts. Western blot analyses was done to examine the effect of biomaterial on collagen synthesis by cells and compared to cells grown in the presence of growth factors. This work demonstrated an uncomplicated way of identifying components that synergistically promote healing. Besides, we demonstrated that modulating local wound environment using biomaterials with bioactive compounds could enhance healing. This study finds that the developed biomaterials offer immense scope for healing wounds by means of their skin regenerative features such as anti-inflammatory, fibroblast stimulation for collagen secretion as well as inhibition of enzymes and markers impeding the healing, hydrodynamic properties complemented with other features including non-toxicity, biocompatibility, and safety.